KRITIK TERHADAP KONSEP TANZIL NASR HAMID ABU ZAYD DAN IMPLIKASINYA TERHADAP STATUS AL-QUR’AN (TAJDID: Jurnal Ilmu Ushuluddin, 2019)
This paper intends to present Tanzil Nasr Hamid Abu Zayd's ideas or concepts and their implications for the status of the Qur'an, to then provide adequate criticism of it. In the first section, the concept of Tanzil, according to Nasr Hamid, which was later imitated by several Indonesian thinkers, will then seek relevance to the ideas put forward by Orentalis. The second part, the implication of the concept of Tanzil Nasr Hamid on the status of the Qur'an, which in it breaks down the new terms of the Qur'an are cultural products (muntaj thasaqafi), Producers of Culture (muntij thasaqafi) and language texts (lashawi nash) the third part is followed by a critical analysis of the concept of Tanzil Nasr Hamid and the implications of Nasr Hamid's tanzil concept on the status of the Qur'an. Tulisan ini bermaksud untuk memaparkan gagasan atau konsep Tanzil Nasr Hamid Abu Zayd dan Implikasinya terhadap status Al-Qur’an, untuk kemudian memberikan kritik yang memadai terhadapnya. Pada bagian pertama, akan dipaparkan tentang konsep Tanzil menurut Nasr Hamid yang kemudian ditiru oleh beberapa pemikir Indonesia, baru kemudian mencari relevansinya dengan gagasan yang dikemukakan oleh Orentalis. Bagian kedua, Implikasi konsep Tanzil Nasr Hamid terhadap status Al-Qur’an, yang didalamnya mengurai terma-terma baru tentang al-Qur’an adalah produk budaya (muntaj thasaqafi), Produsen Budaya (muntij thasaqafi) dan teks bahasa (nash lughawi).bagian ketiga ialah dilanjutkan dengan analisis kritis terhadap konsep Tanzil Nasr Hamid dan Implikasi konsep tanzil Nasr Hamid terhadap status al-Qur’an.